A metriorhynchid crocodyliform braincase from northern Chile - Fernández, Marta Susana (2011)
A three-dimensionally preserved metriorhynchid braincase from the Oxfordian of northern Chile is described. The specimen is referred to the metriorhynchid Metriorhynchus cf.M. westermanni. The excellent preservation provides clear sutures and a detailed description, and X-ray computed tomographic (CT) scanning provides internal anatomical details. The general pattern of the orbitotemporal region is consistent with that of the basal thalattosuchian Pelagosaurus typus as described recently. The specimen from northern Chile shares with other metriorhynchids (e.g., Cricosaurus araucanensis, Metriorhynchus westermanni, M. casamiquelai, and Dakosaurus andiniensis) a dorsally exposed laterosphenoid, a laterosphenoidprootic suture forming a blunt crest separating the supratemporal fenestra into two fossae for muscular attachment, and the quadrate incompletely sutured to the braincase. Thus, these features characterize not only basal but derived Thalattosuchia, as suggested by previous authors. The main difference in the orbitotemporal region is that in the specimen described herein, and in the other metriorhynchids examined, the trigeminal fossa is developed mainly caudal to the trigeminal foramen, whereas in P. typus the fossa is developed rostral and caudal to the trigeminal foramen. CT scanning indicates the presence of enlarged dorsal dural venous sinuses overlying the brain, as it has been described recently in Steneosaurus pictaviensis, and a well-developed sinus within the quadrate. The large foramen ventrolateral to the occipital condyle, which characterizes metriorhynchids, is confirmed as the entry for the internal carotid artery.Metriorhynchus cf.M. westermanni. The excellent preservation provides clear sutures and a detailed description, and X-ray computed tomographic (CT) scanning provides internal anatomical details. The general pattern of the orbitotemporal region is consistent with that of the basal thalattosuchian Pelagosaurus typus as described recently. The specimen from northern Chile shares with other metriorhynchids (e.g., Cricosaurus araucanensis, Metriorhynchus westermanni, M. casamiquelai, and Dakosaurus andiniensis) a dorsally exposed laterosphenoid, a laterosphenoidprootic suture forming a blunt crest separating the supratemporal fenestra into two fossae for muscular attachment, and the quadrate incompletely sutured to the braincase. Thus, these features characterize not only basal but derived Thalattosuchia, as suggested by previous authors. The main difference in the orbitotemporal region is that in the specimen described herein, and in the other metriorhynchids examined, the trigeminal fossa is developed mainly caudal to the trigeminal foramen, whereas in P. typus the fossa is developed rostral and caudal to the trigeminal foramen. CT scanning indicates the presence of enlarged dorsal dural venous sinuses overlying the brain, as it has been described recently in Steneosaurus pictaviensis, and a well-developed sinus within the quadrate. The large foramen ventrolateral to the occipital condyle, which characterizes metriorhynchids, is confirmed as the entry for the internal carotid artery.